Sleep-related breathing disorders in patients with heart failure: current aspects of treatment. Part II - K. S. Krupichka; M. V. Agaltsov; R. P. Myasnikov; O. M. Drapkina (Российский кардиологический журнал)
The second part of the review highlights treatments for different types of sleep apnea in patients with heart failure. In both obstructive and central sleep apnea, ventilatory support during sleep takes a special place in treatment. Therefore, the review details the role of different ventilation modes (in particular, CPAP therapy and adaptive servo-ventilation), analyzes available evidence-based medicine data. The role of low-flow oxygen therapy, surgical treatment, implantable devices, specific therapy (theophylline, acetazolamide) in the treatment of central sleep apnea is also shown, and a novel method of treating central sleep apnea is considered — phrenic nerve stimulation.